Transcriptome combined single-cell sequencing explores molecular mechanisms of ANGPTL4 in sepsis-induced acute lung injury - Ying Qi; Changqi Zhou; Bing Chen (PLoS ONE, 2025)
Objective Sepsis-induced acute lung injury (ALI) constitutes a critical clinical syndrome associated with high mortality rates, yet its molecular mechanisms remain inadequately elucidated. Recent evidence indicates that ANGPTL4 may influence inflammatory responses and endothelial barrier integrity; however, its cell-specific regulatory mechanisms in sepsis-associated ALI are not well understood. This study utilizes transcriptome profiling combined with single-cell sequencing to systematically analyze the spatiotemporal expression patterns and functional networks of ANGPTL4 during the progression of ALI. Methods Gene expression profiles from acute lung injury patients were obtained from the Gene Expression Omnibus (GEO) database. Single-cell and intercellular communication analyses identified candidate gene sets. GSEA examined gene-immune cell relationships, while gene enrichment analysis explored key gene mechanisms. miRNA networks identified target miRNAs for these key genes. Molecular docking with AutoDock and the CTD database predicted drugs interacting with ANGPTL4. Additionally, in vitro experiments confirmed the Angptl4 gene expression level in sepsis-induced acute lung injury. Results Angptl4 is a crucial marker for acute lung injury progression, potentially affecting pathways like the pentose phosphate pathway, fatty acid degradation, and PPAR signaling. It may interact with Q9BY76-Quercetin, but this requires further investigation. In vitro studies show a notable increase in Angptl4 expression compared to controls. Conclusion The increased expression of ANGPTL4 may influence disease progression through mechanisms involving fatty acid metabolism, PPAR signaling, and the pentose phosphate pathway in murine models. Furthermore, its dual role in regulating inflammation through interactions with both pro-inflammatory and anti-inflammatory cells underscores its pivotal contribution to the pathogenesis of acute lung injury (ALI), thereby supporting the development of targeted therapies for sepsis-induced lung injury.